Świętochowski’s Positivist Musings on Science as the Engine of Civilizational Progress - Szotek, Barbara (Folia Philosophica, 2021)
Positivist philosophy is focused on the problem of science and especially on its cognitive results and applications. We can say that Polish intellectual circles of this era glorified science. In her article, Barbara Szotek presents this phenomenon through the figure of Aleksander Świętochowski, the most famous representative and ideologist of scientific positivism. His works best illustrate the evolution of positivist views on science and its social role.